PENGARUH INOVASI PELAYANAN MELALUI APLIKASI SI D’NOK TERHADAP KUALITAS PELAYANAN PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA SEMARANG - Khasanah, Syifa Uswatun; Priyadi, Budi Puspo; Purnaweni, Hartuti (Journal of Public Policy and Management Review, 2024)
The quality of public services at the Semarang City Dukcapil Disdukcapil is influenced by public service innovation through the SI D'Nok innovation, however based on data found in the field there are still several problems with the SI D'Nok innovation. The aim of this research is to determine and test the effect of Service Innovation through SI D'Nok on Service Quality at the Semarang City Population and Civil Registration Service. The population of this research is people who have applied for population administration through SI D'Nok, totaling 100 people and was determined using an accidental sampling technique taken based on intervals. The measuring instrument used is the Likert scale. Data analysis uses a simple linear regression test and the coefficient of determination test. The research results show that there is Service Innovation through SI D'Nok on Service Quality at the Semarang City Population and Civil Registration Service. The simple linear regression test shows a value of 0.000<0.05. The linear regression test and coefficient of determination test show a value of 0.000<0.05 with an influence contribution of 46.7% for the influence of service innovation through SI D'Nok on Service Quality at the Semarang City Population and Civil Registration Service.